SAMM50 Affects Mitochondrial Morphology through the Association of Drp1 in Mammalian Cells. Issue 9 (15th April 2016) - Liu, Shuo; Gao, Yali; Zhang, Cheng; Li, Han; Pan, Shiyi; Wang, Xiaoli; Du, Shiming; Deng, Zixin; Wang, Lianrong; Song, Zhiyin; Chen, Shi
Abstract : Mitochondrial fission and fusion activities are important for cell survival and function. Drp1 is a GTPase protein responsible for mitochondrial division, and SAMM50 is responsible for protein sorting and assembly. We demonstrated that SAMM50 overexpression results in Drp1‐dependent mitochondrial fragmentation in HeLa cells. However, the mitochondrial fragmentation induced by SAMM50 overexpression could be reversed through co‐expression with MFN2. Furthermore, SAMM50 interacts with Drp1 both in vivo and in vitro . The mitochondria in SAMM50 knockdown HeLa cells displayed a swollen phenotype, and the levels of the SAM complex and OPA1, along with the mitochondrial Drp1 levels, significantly decreased. In addition, mitochondrial inheritance was impaired in SAMM50 silenced cells. These results suggest that SAMM50 affects the Drp1‐dependent mitochondrial morphology. Abstract :